Kemampuan pemahaman konsep matematis dan minat belajar melalui model pembelajaran TGT berbantuan Genially - Mahyuni, Sabrina; Mujib, Mujib; Negara, Hasan Sastra; Mardiyah, Mardiyah (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2024)
Understanding mathematical concepts is the understanding ability that students must have in mastering learning concepts and applying them in everyday life. This research aims to determine the influence of the TGT learning model assisted by Genially on the ability to understand mathematical concepts and interest in learning, the influence of the TGT learning model assisted by Genially on the ability to understand mathematical concepts, and the influence of the TGT learning model assisted by Genially on interest in learning. The research sample was students in classes VIII H, VIII I, and VIII J of SMPN 1 Natar. The sampling technique uses cluster random sampling by collecting data in the form of tests and questionnaires. The test uses MANOVA test analysis. Based on the results of the analysis and discussion, it was concluded that there was an influence of the Genially assisted TGT model on understanding mathematical concepts and interest in learning, there was an influence of the Genially assisted TGT model on understanding mathematical concepts, and there was an influence of the Genially assisted TGT model on interest in learning.